A comparative study on chemical and cooking properties of abiotic stress tolerant and other high yielding rice varieties in Bangladesh - Matin, A; Siddiquee, MA; Akther, S; Alam, MK; Ali, MS (Bangladesh Journal of Agricultural Research, 2018)
The experiment was conducted to know the chemical and cooking properties of nineteen BRRI released high yielding rice varieties (HYVs) including salinity, drought and submergence tolerant varieties. All the rice varities were grown in normal condition. Among the HYVs, amylose content of the varieties range from 19 to 27.0% and BRRI dhan47 contained the highest amylose content (27%). The highest amount of protein (9.3%) was found in BRRI dhan56 followed by BRRI dhan42 (9%) and BRRI dhan43 (8.8%). Alkali spreading value ranged from 3.0 to 7.0. Maximum cooking time (20.5 min.) was required in the variety of BRRI dhan40. Alkali spreading value was found significantly and negatively correlated with cooking time. The kernel elongation ratio was greater than 1.1 in all the varieties except BRRI dhan62. The imbibition ratio was greater than 3.0 in all the varieties except BRRI dhan43 and BRRI dhan61. There were no significant differences between non-abiotic and abiotic stress tolerant varities in respect of chemical and cooking properties because all varities were grown in normal condition. Bangladesh J. Agril. Res. 42(4): 673-679, December 2017